ΔNp73β is oncogenic in hepatocellular carcinoma by blocking apoptosis signaling via death receptors and mitochondria - Schuster, André; Schilling, Tobias; De Laurenzi, Vincenzo; Koch, Andreas Franz; Seitz, Sarah Janina; Staib, Frank; Teufel, Andreas; Thorgeirsson, Snorri S.; Galle, Peter; Melino, Gerry; Stremmel, Wolfgang; Krammer, Peter H.; et al. (Cell cycle, 2010)
p73 belongs to the p53 family of transcription factors known to regulate cell cycle and apoptosis. The Trp73 gene has two promoters that drive the expression of two major p73 isoform subfamilies: TA and ΔN. In general, TAp73 isoforms show proapoptotic activities, whereas members of the N-terminally truncated (ΔN) p73 subfamily that lack the transactivation domain show antiapoptotic functions. We found that upregulation of ΔNp73 in hepatocellular carcinoma (HCC) correlated with reduced survival. Here, we investigated the molecular mechanisms accounting for the oncogenic role of ΔNp73 in HCC.
Gesehen am 06.07.2023